Cieśla i krzyż - Kozłowski, Jan M. (Vox Patrum, 2013)
A close relationship exists between Jesus’ death on the cross and the fact that Jesus was a carpenter. Wood, from which the tool of Jesus’ execution was fashioned, was also the dominant element of the Son of God’s everyday experience. In the light of this correspondence one can see God’s plan, according to which there is a strong link not only between Nazareth and Golgotha, but also between the „cross” carried by a Christian and the content of his everyday life.